A Continuous Logit Hotelling Model with Endogenous Locations of Consumers - Wrede, Matthias (Economics letters, 2015)
This paper analyzes location and price choices of firms and subsequent location choices of consumers in a linear city model when consumers have different perceptions of locations and firms. The study utilizes a continuous logit model to describe consumers’ location and supplier choices. A unique subgame perfect Nash equilibrium exists where firms make positive profits and the minimum differentiation principle applies. For identical firms, prices converge to marginal costs as heterogeneity of consumers’ perceptions disappears.
Keywords: Spatial competition; Continuous logit model; Minimum differentiation principle